1990
DOI: 10.3758/bf03205014
|View full text |Cite
|
Sign up to set email alerts
|

Perceived lightness, but not brightness, of achromatic surfaces depends on perceived depth information

Abstract: Three experiments wereconducted in an attempt to replicate and clarify Gilchrist's ( ,1980 experiments on the effects of depth information on judgments of achromatic surface color. Gilchrist found that coplanarity, and not retinal adjacency, was the dominant factor in determining achromatic color matches. Because such matches can be made on the basis of either brightness or lightness, we obtained judgments of both qualities. Stereopsis was added to enhance the perceived depth effect of Gilchrist's display, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 24 publications
(39 reference statements)
9
62
2
Order By: Relevance
“…1, left). Schirillo et al (1990) found that observers' judgments of the brightness of the gray paper did not vary significantly between the near and far conditions. Instead, because it was actually under a constant level of illumination in both conditions (i.e., the lower level of illumination of the near room), its brightness remained constant across conditions.…”
Section: The Problem With Collapsing a Three-dimensional World Into Tmentioning
confidence: 94%
See 1 more Smart Citation
“…1, left). Schirillo et al (1990) found that observers' judgments of the brightness of the gray paper did not vary significantly between the near and far conditions. Instead, because it was actually under a constant level of illumination in both conditions (i.e., the lower level of illumination of the near room), its brightness remained constant across conditions.…”
Section: The Problem With Collapsing a Three-dimensional World Into Tmentioning
confidence: 94%
“…To see how the two distinct qualities of lightness and brightness differ, Schirillo and colleagues (Schirillo, Reeves, & Arend, 1990) repeated Gilchrist's experiment simulated with a special-purpose Tektronix CRT and stereoscope to generate three-dimensional space and the same physical variations in intensity as Gilchrist. Although the main interest was in the difference between lightness and brightness, the data also revealed a striking contrast with those of Gilchrist: While the effects on lightness judgments in the simulation were in the same direction as his, the magnitude was only 41 % of his; that is, the lightness range of the gray paper that appeared in either the near or the far room spanned a 2.7:1 ratio, as compared to his 6.6:1 ratio.…”
Section: The Problem With Collapsing a Three-dimensional World Into Tmentioning
confidence: 99%
“…For example, lightness perception can depend on the geometric interpretation of a visual scene, such as curvature (Knill & Kersten, 1991;Pessoa, Mingolla, & Arend, 1996), transparency (Adelson, 1993), and depth (Gilchrist, 1977;Schirillo & Arend, 1995;Schirillo, Reeves, & Arend, 1990). Also, simply inducing the observer to interpret a scene differently (whether a luminance boundary is a shadow or an object border) affects lightness accordingly (Gilchrist, Delman, & Jacobsen, 1983).…”
Section: The Problem Of Lightness Constancymentioning
confidence: 99%
“…Several investigations have shown that brightness matches are not illumination invariant (e.g., Arend & Goldstein, 1987;Jacobsen & Gilchrist, 1988;Schirillo, Reeves, & Arend, 1990). Moreover, for increment conditions where the test region is immediately surrounded by a lower reflectance region, brightness matches follow luminance rather closely.…”
mentioning
confidence: 99%